2017
DOI: 10.1292/jvms.16-0355
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiological study of rodent-borne hepatitis E virus HEV-C1 in small mammals in Hanoi, Vietnam

Abstract: There is concern about the zoonotic potential of rodent-borne hepatitis E virus, designated as HEV-C1. However, epizootiological information about HEV-C1 is limited. To address this issue, serum samples from 443 small mammals captured at 5 sites in Hanoi, Vietnam, were examined for anti-HEV-C1 IgG antibodies. In addition, livers of seropositive animals were examined for viral RNA. Anti-HEV-C1 antibodies were detected in 57 (12.9%) of the 443 serum samples. Seropositive animals were found in all of the sites (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Since 2010, HEV-C1 RNA and antibodies have gradually been detected in rats on the Eurasian continent, North American continent, and the Indonesian archipelago [6,19,20,21,22,23,24,25]. This study further documents the rst detection of HEV-C1 in rats in Taiwan, a geographically isolated island.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Since 2010, HEV-C1 RNA and antibodies have gradually been detected in rats on the Eurasian continent, North American continent, and the Indonesian archipelago [6,19,20,21,22,23,24,25]. This study further documents the rst detection of HEV-C1 in rats in Taiwan, a geographically isolated island.…”
Section: Discussionsupporting
confidence: 57%
“…Overall, we observed that 52% of wild rats were seropositive for rat HEV in international ports in Taiwan. This prevalence rate is higher than that of early studies, including 4.1-18.1% in Indonesia [19,20], 12.9% in Vietnam [21], 23.3% in China [22], 24.5% in Germany [23], 27.9% in Japan [24], and 31.2% in Lithuania [25]. However, the seropositive rates between studies might be di cult to directly compare due to the lack of identical antigens and detection antibodies used in the ELISA tests.…”
Section: Discussionmentioning
confidence: 67%
“…In Vietnam, animals captured at bus stations and hospitals have tested positive for rat HEV 48 . These findings are supported by serological evidence from domestic animals and rodents in other studies 45,49,50 .…”
Section: Fernandes Et Al (2019)mentioning
confidence: 99%
“…In Japan, the rates were 31.5% (114/362) from 2000 through 2002, while another study with unreported sample collection dates resulted in 28.6% seroprevalence (16/56) [22,23]; in Germany, the seroprevalence was 24.5% (36/147) between 2007 and 2010 [24], comparable to China with 27.8% (64/230) between 2011 and 2012 [25]. In Vietnam, two separate studies revealed similar seroprevalences of 20.3% (25/123) and 22.3% (21/94) in 2011 and an additional study between 2012 and 2013 demonstrated a lower seroprevalence of 12.3% (48/389) [26][27][28]. In a recent study in Lithuania, the seroprevalence was 31.2% (34/109) between 2014 and 2017; however, data were derived from both Norway rats (27) and Black rats (82) and individual species rates were not indicated [29].…”
Section: Seroprevalence Of Anti-hev Antibodiesmentioning
confidence: 85%
“…Three studies in Vietnam found anti-HEV seroprevalences in Rattus tanezumi (Oriental house rat) of 25.0% (4/16) and 33.3% (2/6) in 2011 and 19.6% (9/46) between 2012 and 2013 [26][27][28]. In a large-scale investigation of sera of wild rats in China between 2011 and 2012, anti-HEV IgG rates in the species Rattus rattoides losea (Losea rat), Rattus flavipectus (Yellow-breasted rat), Rattus rattus hainanus, and Bandicota indica (Greater bandicoot rat), were 21.5% (26/121), 19.9% (34/171), 11.8% (2/17), and 23.0% (40/174), respectively [25].…”
Section: Seroprevalence Of Anti-hev Antibodiesmentioning
confidence: 99%